Patterns and factors of intergenerational social mobility by education: a case of Malay agricultural community in FELDA Trolak Utara, Perak, Malaysia - Fakhruddin, Faizah Mohd; Mohd Noor, Noor Azlan; Mahfar, Mastura; Fakhruddin, Fathiyah Mohd; Abd. Hamid, Mohd Azhar; Abdull Rahman, Rabeatul Husna; Rusbadrol, Noraini (Human Resource Management Academic Research Society, 2023)
This study discusses the issues of intergenerational social mobility by education experienced by two generations of Malay families in a Malay agricultural community namely, FELDA Trolak Utara, Perak, Malaysia. The objectives of the study are to examine the patterns of social mobility and to analyse the socio-cultural factors that are responsible for the different patterns of intergenerational social mobility by education experienced by two generations of the Malay family organizations in FELDA. The study involved fieldwork conducted from December 2014 to August 2015 for a period of nine months. The study employed the qualitative method using participant observation and in-depth interviews, using an interview schedule with thirty families and two FELDA key personalities. The same informants were interviewed again in a follow-up study conducted in November and December 2022 to explore changes that might happen especially during the post-pandemic period which involved only e-mails, telephone calls, or text messages. The findings of the study show that the majority of the informants experienced a pattern of upward intergenerational social mobility in terms of their level of education. Although horizontal intergenerational social mobility was also International Journal of Academic Research in Business and Social Sciences Vol. 1 3 , No. 6, 2023, E-ISSN: 2222-6990 © 2023 HRMARS 24 observed, nevertheless the cases were very limited in number. Interestingly, no notable change in the pattern was found in the follow-up study during the post-pandemic period. Social factors such as family institutions, major roles played by the Malaysian government, and individuals’ positive attitudes towards education in particular, had contributed to the immense incidence of upward intergenerational social mobility. On the other hand, intractable factors such as war, poverty, religious beliefs, and cultural traditions were found to be the obstacles faced by the first-generation informants in particular. This study provides some fresh and interesting insights into the sociological body of knowledge, especially in intergenerational social mobility studies. Finally, this study further suggests a number of possible avenues for future research on intergenerational social mobility that could not be covered by this study. This includes comparative studies among different ethnic groups and areas of residence and large-scale studies using a quantitative approach.